(untitled) (Revista Sistemas de Producción Agroecológicos, 2018)
The Orinoquia is characterized by its great native and commercial forest wealth, throughout time, research has been developed in order to promote their development and the different uses of plant species. In this research, the extraction of tannins from the bark of trees found in the Orinoquia region of Colombia was evaluated. The evaluated species were pine (Pinus caribaea), acacia (Acacia mangium) and eucalyptus (Eucalypto pellita). A selection of the barks of the mentioned trees was made to dry them and then grind them, and thus be able to reduce its particles to a size of 1 mm, a solid-liquid leaching operation was carried out to evaluate the following factors: NaOH concentration: 1 and 5%, solid-liquid ratio (S/L): 1/60, 1/90 and 1/120, and extraction temperature: 70 and 80°C, observing the effect on the percentage of extraction yield of tannins. A statistical analysis was carried out in the R-Project program, using the Fisher test with 95% reliability. It was obtained as a result that the bark with the highest production was pine under conditions of 5% NaOH, S/L ratio of 1/90 and temperature of 80°C, in eucalyptus, better yields were obtained with 5% NaOH, 1/120 and 80°C, finally, in acacia the best performance was observed with 1% NaOH, 1/90 and 80°C (P<0.05). It is concluded that the temperature does not directly influence the extraction performance, since the difference between the two levels was not important, otherwise it was observed with the alkalinity factors and the S/L ratio, obtaining higher yields with 5% Vs 1% NaOH and a solvent solute ratio 1/90 Vs 1/60 and 1/120.